Current Aspects of Legal Regulation for Monitoring Electronic Communications and Removal of Information from Electronic Communication Networks in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The article is focused on studying current aspects of normative and legal regulation for monitoring electronic communications in foreign countries and in Ukraine; on the features of conducting search and investigative actions on the removal of information from electronic communication networks.The legislation of Ukraine does not currently provide the procedure for creation and implementation of interception systems for electronic communications, does not define organizational and technical requirements that should guarantee conditions for monitoring such activities, despite the relevance of modern legal regulation of conducting search, operative and technical measures in communication networks. rapid development of electronic information technology.The legislator made an attempt to legally regulate the implementation of operative and technical measures in electronic communication networks in the Criminal Procedural Code of Ukraine dated from April 13, 2012, which provided the removal of information from transport telecommunication networks. Relevant norms were also provided in the Law of Ukraine “On Operative and Search Activities”. Regarding the dynamic development of legislation, which is primarily due to the adoption of the Law of Ukraine “On Electronic Communications” dated from December 16, 2020, the author of the article has stated the need to update the existing procedure for such activities.The author has suggested measures, the realization of which should improve the capacity of authorized law enforcement agencies to combat crime in the field of information and communication technologies: adoption of the Law of Ukraine “On Interception of Electronic Communications”, amendments to the Laws of Ukraine “On Electronic Communications”, “On Operative and Search Activities”, “On Counterintelligence Activities”, “On Combating Terrorism”; bringing the norms of domestic legislation in line with the provisions of the Convention on Cybercrime; creation of conditions necessary to improve the capacity of authorized state agencies to remove information from electronic communication networks; establishing proper cooperation with foreign law enforcement agencies.
Keywords: electronic communications; networks; monitoring; interception; removal of information; legal regulation.